TB/HIV integration at primary care level: A quantitative assessment at 3 clinics in Johannesburg, South Africa - L Page-Shipp; Y Voss de Lima; K Clouse; J de Vos; L Evarts; J Bassett; I Sanne; A Van Rie (AOSIS, 2012)
Background. In 2004 the World Health Organization (WHO) released the Interim Policy on Collaborative TB/HIV activities. According to the policy, for people living with HIV (PLWH), activities include intensified case finding, isoniazid preventive therapy (IPT) and infection control. For TB patients, activities included HIV counselling and testing (HCT), prevention messages, and cotrimoxazole preventive therapy (CPT), care and support, and antiretroviral therapy (ART) for those with HIV-associated TB. While important progress has been made in implementation, targets of the WHO Global Plan to Stop TB have not been reached. Objective. To quantify TB/HIV integration at 3 primary healthcare clinics in Johannesburg, South Africa. Methods. Routinely collected TB and HIV data from the HCT register, TB 'suspect' register, TB treatment register, clinic files and HIV electronic database, collected over a 3-month period, were reviewed. Results. Of 1 104 people receiving HCT: 306 (28%) were HIV-positive; a CD4 count was documented for 57%; and few received TB screening or IPT. In clinic encounters among PLWH, 921 (15%) had documented TB symptoms; only 10% were assessed by smear microscopy, and few asymptomatic PLWH were offered IPT. Infection control was poorly documented and implemented. HIV status was documented for 155 (75%) of the 208 TB patients; 90% were HIV-positive and 88% had a documented CD4 count. Provision of CPT and ART was poorly documented. Conclusion. The coverage of most TB/HIV collaborative activities was below Global Plan targets. The lack of standardised recording tools and incomplete documentation impeded assessment at facility level and limited the accuracy of compiled data.